2014
DOI: 10.1111/cid.12265
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐Implantitis Associated with Type of Cement: A Retrospective Analysis of Different Types of Cement and Their Clinical Correlation to the Peri‐Implant Tissue

Abstract: The frequency of undetected excess cement depends essentially on the type of cement used. Cements that tend to leave more undetected excess have a higher prevalence for peri-implant inflammation and cause a more severe peri-implant bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 17 publications
2
64
0
Order By: Relevance
“…Studies have shown that, in the presence of excess cement at the crown-abutment interface, periimplant mucosal inflammation or bone loss occurs 80% to 85% of the time. [57][58][59] The use of certain cement, for example, methacrylate-based cement, is associated with increased residual cement and consequently a higher prevalence for peri-implant diseases 57,60 because they are less viscous 60 and also more susceptible to bacterial invasion. 61 In contrast, zinc oxide eugenol-containing cements are more viscous, thus, easier to remove and can inhibit biofilm growth at the crown-abutment interface.…”
Section: Prosthetic Considerationsmentioning
confidence: 99%
“…Studies have shown that, in the presence of excess cement at the crown-abutment interface, periimplant mucosal inflammation or bone loss occurs 80% to 85% of the time. [57][58][59] The use of certain cement, for example, methacrylate-based cement, is associated with increased residual cement and consequently a higher prevalence for peri-implant diseases 57,60 because they are less viscous 60 and also more susceptible to bacterial invasion. 61 In contrast, zinc oxide eugenol-containing cements are more viscous, thus, easier to remove and can inhibit biofilm growth at the crown-abutment interface.…”
Section: Prosthetic Considerationsmentioning
confidence: 99%
“…Cement retained implant restoration has issues including irretrievability and difficulty of controlling the cement excess beyond the abutment joint. The cement excess can be a major cause of peri-implantitis [1315]. Screw-retained implant restoration has also some disadvantages including the difficulty to get a right positioning of the access-hole compatible with a suitable aesthetic appearance and the aesthetic result of the access-hole restoration [16].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, even when careful and appropriate technique is used for cementation, selection of cement type remains an important component of the therapeutic procedure. In a retrospective study, Korsch and Walther 20 found a remarkably high percentage of implants cemented with methacrylate cement having cement excess (62%) and mucosal inflammation (94% to 100%) compared to a zinc oxide‐cemented group. After removal of the methacrylate cement and recementation of the implant crowns with zinc oxide cement, a reduction in BOP of >75% of the cases was observed 16 .…”
Section: Discussionmentioning
confidence: 99%